The Influence of the Geometry of Movement during the Friction Process on the Change in the Tribological Properties of 30CrNiMo8 Steel in Contact with a G40 Steel Ball - Kohutiar, Marcel; Krbata, Michal; Escherova, Jana; Eckert, Maros; Mikus, Pavol; Jus, Milan; Polášek, Miroslav; Janík, Róbert; Dubec, Andrej (Materials, 2023)
Experiments with changes in motion geometry can provide valuable data for engineering and development purposes, allowing a better understanding of the influence of tribological factors on the performance and service life of joints. The presented subject article focused on the experimental investigation of the influence of the geometry of the movement of the friction process on the change in the tribological properties of 30CrNiMo8 steel. The friction process was carried out without the use of a lubricant in contact with a steel ball of G40 material with a diameter of 4.76 mm. The steel ball performed two types of movement on the surface of the experimental material. The first method used was ball on disc, in which the ball moved reciprocally in an oval direction at an angle of 180° on a circumferential length of 35 mm at a speed of 5 mm/s. The second method consists of the same input parameters of the measurement, with the difference that the path along which the ball moved had a linear character. The load during the experiment was set at a constant value of 50 N with 1000 repetitions. The results show that with the ball on disc method, there was an increase in wear by 147% compared to the linear test method, which was approximately a coefficient of increase in wear of 2.468. EDS analysis pointed to the occurrence of oxidative wear that affected the resulting COF values, which were lower by 8% when using the ball on disc method due to a more uniform distribution of O and C on the surface of the friction groove where these elements acted as solid microlubricants. With the ball on disc method, defects in the form of microcracks occurred, which affected the reduction in the values of the depth of the affected area of microhardness.